Vulnerability of Mountain Communities to Climate Change And Adaptation Strategies - Lama, Sarina; Devkota, Bhupendra (Journal of Agriculture and Environment, 2009)
Climate Change, one of the most important global environmental challenges facing humanity, has implications on food production, natural eco-systems, fresh water supply and health in Nepal. It is contributing mostly to the rise in air temperature leading to rapid melting of glaciers and increment of glacier lakes. Exploitation of natural resources associated with growing population has led to increasing pollution, declining water quality, land degradation, etc. Extreme climate events including flooding, heavy rainfall, droughts, heat wave and cold stream etc. are also the consequences of climate change in Nepal. Moreover, Nepal is largely dependent on climate-sensitive sectors, such as rain-fed agriculture; its fragile mountain ecosystems and dramatic topography make the country prone to flooding. Due to such events, agricultural productivity is declining with increasing problem of food security in mountainous regions. In recent years, the signs of such changes are being observed and may become more prominent over next couple of decades. Many rural communities are struggling through different adaptation measures as an attempt to reduce the risk of climate change vulnerability. The Journal of Agriculture and Environment Vol:10, Jun.2009 Page: 76-83